Manufactured fibers to fabrics and beyond - Ecklund, Roxanne (New York, NY Insight Media, 2008)
Examines the origins, physical and chemical structures, properties, and uses of manufactured, or manmade, fibers. Covers rayon, lyocell, acetate, and such synthetic fibers as nylon, polyester, and acrylic.
DVD
Host/writer, Roxanne Ecklund ; writer/content editor, Sara Grady ; producer/director James Strzenlinski.
Keywords: Textile fibers, Synthetic; Synthetic fibers industry; Textile fabrics